Performance Pedagogy: Performing Fluxus Pedagogy in a Contemporary Lithuanian Context - Griniuk, Marija (Acta Paedagogica Vilnensia, 2020)
Educators practice performance pedagogy as the method where an educator/facilitator is seen as a performer or actor (Pineau 1994, p. 4). This paper presents an analysis of the historical roots of performance pedagogies in Fluxus pedagogies and performance pedagogy practices within participatory art events in Lithuania as exemplified by festivals AN88 (1988) and AN89 (1989). The case of my research rests on the contemporary implementation of performance pedagogy techniques during the course The Temporary Department of Time, Space, and Action for BA students at the Vilnius Academy of Arts in Lithuania. This research aims to define the concept theories within performance pedagogy in the art academy education, which developed behind the terms Human Semiotics (Andersen 2002), Hyper Performer,1 and InterMedia (Higgins 1984). This project was implemented using the strategy of critical utopian action research in the context of the Vilnius Academy of Arts. The empirical material was gathered during my employment as a guest lecturer and the implementation of my pedagogical internship at the Vilnius Academy of Arts.2These concept theories are defined through. a reflexive analysis of archive material on the historical origin of performance pedagogies, originating in Fluxus pedagogies, local Lithuanian participatory art, and data from the contemporary case of my project The Temporary Department of Time, Space and Action (2018), in the form of archive material, photographs, interviews, observations, notes, and my diary. The results of this research are the application of performance pedagogy concepts and terminology to the art and education projects and the definition of the key concept theories within this field. These results can be useful for artists and those practicing university pedagogy.
Keywords: academy; art; education; Fluxus; performance; Lithuania